Employing drilling technique in teaching English writing skills to a group of rural Malaysian students - Suyansah Swanto; Wardatul Akmam Din (International Institute for Science, Technology and Education (IISTE), 2014)
In this research, the researcher has focused on the use of drilling technique or repetition drill (Freeman, 2000: 48) in a mixed gender rural Malaysian classrooms for both control and treatment group. Besides that, it was used among limited proficiency students and their level are very poor whereby they cannot write even in using the simplest of English. It is a technique that allows and helped the students in writing because they are exposed to lessons that are drill-and-practice based on hierarchical skill sequence with few extended writing opportunities. This study also examines the students’ level of confidence after using the drilling technique. It is hoped that incorporating this technique in the classroom can help to improve students’ writing especially for the descriptive writing part, which make the time and effort in carrying out this study and using this technique worthwhile.